Targeting Bcl-2 Family of Proteins: An Important Strategy in Cancer Therapeutics - T. Makhija, Dinesh; R. Somani, Rakesh; P. Kalantri, Pushkar (Current Chemical Biology, 2011)
BCL-2 protein controls the intrinsic pathway of apoptosis and plays a crucial role in governing apoptotic cell death. It regulates mitochondrial outer membrane permeability, leading to the initiation of Caspase cascade. Till date there are 25 genes known to be the members of BCL-2 family. Some of them are pro-apoptotic and some are anti-apoptotic. Over expression of anti-apoptotic BCL-2 proteins has been observed in 80% of beta cell lymphomas and 90% of colorectal adenocarcinomas. Hence, BCL-2 proteins are valuable targets in designing anti-cancer agents. Peptides, Peptidomimetics and non-peptide antagonists are designed to trigger apoptosis by BCL-2 pathway. These drugs have exhibited promising results at pre-clinical and clinical levels. It is well known that apoptosis is also related to inflammatory responses; it will be interesting to explore the area of BCL-2 to design some drugs having anti-inflammatory action. This review gives an account of development of BCL-2 family of proteins as potential target in the varieties of diseases including special focus on cancer.
Keywords: Extrinsic